The Political Behavior of the Power Elite in the Kurdistan Region - Iraq after 2003 - Hameed, Hoshyar J. (Mitanni Journal of Humanitarian Sciences, 2023)
This research tries to trace the path of political behavior of the power elite in the Kurdistan Region - Iraq after 2003, within the literature of political systems and its relationship to changing the priorities of the elite (decision makers), and thus transforming some patterns of the work of that elite, the behavior of the elite in general is a reflection of the values ​​that He receives it from the society in which he is raised and receives from it its social upbringing, for the interaction between elite behavior and society that aims to achieve the common good is one of the constant foundations of the democratic nature that characterizes the advanced social system. This interaction exists between the behavior of the elite and society and expresses itself in its behavior in various fields of life. That society, with its social system and the legislated political behavior, are moving together on the right path, the path of progress, advancement and prosperity.